Needle preceding the scalpel in soft-tissue sarcomas – A case series - Vikram R; Rashmi MV; Nischita Budihal; Kanaka R (Asian Journal of Medical Sciences, 2023)
Soft-tissue sarcomas (STSs) are rare neoplasms that can be initially evaluated by fine-needle aspiration cytology (FNAC). Although they are difficult to subtype, these sarcomas can be graded and classified based on cytomorphology. FNAC, with clinical and radiological correlation, can be effectively used in the diagnosis of STSs. Application of ancillary techniques is essential to arrive at the final diagnosis. The aim of the study was to determine the efficacy of FNAC in the initial diagnosis of STSs. Three patients who presented with soft-tissue masses were initially evaluated by ultrasound and/or magnetic resonance imaging and FNAC. Following which, all the three cases were operated on and studied on histopathology and immunohistochemistry to arrive at a final diagnosis. All the three cases were diagnosed as malignant on FNAC even when radiology findings differed or was not confirmatory in one case. FNAC diagnosis was appropriate in case of grading of tumors and classification based on morphology in all the three cases. FNAC of soft-tissue tumors (STTs) is a quick, reliable, and cost-effective mode of initial investigation for STTs. Although it is difficult to subtype the diagnosis, in majority of the cases, a diagnosis of benign or malignant and grade of the tumor can be assessed.